2018
DOI: 10.1007/s00586-018-5813-8
|View full text |Cite
|
Sign up to set email alerts
|

Anterior controllable antedisplacement fusion as a choice for 28 patients of cervical ossification of the posterior longitudinal ligament with dura ossification: the risk of cerebrospinal fluid leakage compared with anterior cervical corpectomy and fusion

Abstract: Purpose To compare the incidence rate of cerebrospinal fluid (CSF) leakage between anterior controllable antedisplacement fusion (ACAF) and anterior cervical corpectomy and fusion (ACCF) in the treatment of ossification of the posterior longitudinal ligament (OPLL) with dura ossification (DO). Methods In the period from June 2015 to June 2017, ACAF and ACCF were performed on patients with OPLL with DO. Double-layer sign was observed on axial bone window of CT images. The operation duration, blood loss, and hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…This technique allows for multilevel decompression to be achieved from an anterior approach without direct manipulation of the OPLL mass [41,42]. In comparison with a traditional ACCF approach, the ACAF technique demonstrated greater radiographic decompression, as well as significantly greater postoperative JOA scores and lower complication rates [41,43]. Another technique is the “skip” corpectomy and fusion (SCF) which aims to provide multilevel decompression while maintaining adequate stabilization [42].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique allows for multilevel decompression to be achieved from an anterior approach without direct manipulation of the OPLL mass [41,42]. In comparison with a traditional ACCF approach, the ACAF technique demonstrated greater radiographic decompression, as well as significantly greater postoperative JOA scores and lower complication rates [41,43]. Another technique is the “skip” corpectomy and fusion (SCF) which aims to provide multilevel decompression while maintaining adequate stabilization [42].…”
Section: Discussionmentioning
confidence: 99%
“…To further minimize the risk of complications with ADF, Yoshii et al [63] have proposed use of intraoperative CT along with the ADF procedure. In a small RCT of 25 patients undergoing ADF using intraoperative CT, the enhanced imaging modality was found to confer better postoperative outcome and a lower rate of complications compared to ADF without intraoperative CT. More recently, the ACAF technique was used to treat to a small cohort of 28 patients with OPLL and evidence of DO, and successfully demonstrated a significantly lower rate of CSF leak with ACAF (3.6%) compared to anterior corpectomy (22.6%, p<0.01) [43].…”
Section: Discussionmentioning
confidence: 99%
“…ACAF combines the advantages of direct decompression as occurs with ACCF with the limited manipulation of the canal contents as occurs with the posterior approach 4-6 . The procedure considers the ossified mass and the vertebral body as a single unit.…”
Section: Rationalementioning
confidence: 99%
“…According to the literature, OPLL has been recognized as a risk factor for the occurrence of CSF leak in spinal surgery. Cervical OPLL usually presents with dura ossi cation (DO), and it is a great technical challenge to separate the ligament from the posterior longitudinal ligament once the ossi ed dura mater is fused with the posterior longitudinal ligament 25 . Hannallah et al 20 reported that the incidence of CSF leak in patients with OPLL after cervical spine surgery was 12.5%, which was 13.7 times higher than that in the group without OPLL, and the data in our survey turned out to be 4.45.…”
Section: Risk Factors For Early Postoperative Csf Leak After Anterior...mentioning
confidence: 99%